GAME REQUIREMENTS GATHERING AMONG HOSPITALISED PAEDIATRIC CANCER PATIENTS: A THEMATIC ANALYSIS - Nordin, A. Imran; Hamzah, Irna Hamil; Rasid, Nadhirah; Baharin, Hanif; Nohuddin, Puteri Nor Ellyza; Alias, Hamidah; Mohamed Hafsah, Nor Hazla; Abdul Kadir, Nor Ba’yah; Mohammad Yatim, Maizatul Hayati; Kassim, Mohd Yazid (Malaysian Journal of Computer Science, 2019)
This paper presents a study that analyzes hospitalized pediatric cancer patients’ routines and activities to inform the game design to be used for the development of a digital game to empower them. This study focuses on discovering patients’ experiences while being hospitalized. The patients’ activities throughout their hospital stay are recorded through non-participatory observations strategy and their experiences inward are gathered through interview sessions with their parents or guardians who have been nursing them during their entire stay in the hospital. The findings suggest that the patients’ experiences are divided into two main themes, namely positive and negative affect. These two themes are depending on the patients’ treatment phases: before, during and after receiving medical treatments. These findings are crucial to being translated into design principles to inform game design. It is important to ensure that the digital game for pediatric cancer patients is designed properly to ensure its suitability to be played by them. The ability to understand the actual routines and experiences in the hospital would help designers and developers of digital games to develop a digital intervention to empower pediatric cancer patients while being hospitalized